Novel hydrophilic nanostructured microtexture on direct metal laser sintered Ti–6Al–4V surfaces enhances osteoblast response in vitro and osseointegration in a rabbit model. Issue 8 (4th May 2016) - Hyzy, Sharon L.; Cheng, Alice; Cohen, David J.; Yatzkaier, Gustavo; Whitehead, Alexander J.; Clohessy, Ryan M.; Gittens, Rolando A.; Boyan, Barbara D.; Schwartz, Zvi
Abstract: The purpose of this study was to compare the biological effects in vivo of hierarchical surface roughness on laser sintered titanium–aluminum–vanadium (Ti–6Al–4V) implants to those of conventionally machined implants on osteoblast response in vitro and osseointegration. Laser sintered disks were fabricated to have micro‐/nano‐roughness and wettability. Control disks were computer numerical control (CNC) milled and then polished to be smooth (CNC‐M). Laser sintered disks were polished smooth (LST‐M), grit blasted (LST‐B), or blasted and acid etched (LST‐BE). LST‐BE implants or implants manufactured by CNC milling and grit blasted (CNC‐B) were implanted in the femurs of male New Zealand white rabbits. Most osteoblast differentiation markers and local factors were enhanced on rough LST‐B and LST‐BE surfaces in comparison to smooth CNC‐M or LST‐M surfaces for MG63 and normal human osteoblast cells. To determine if LST‐BE implants were osteogenic in vivo, we compared them to implant surfaces used clinically. LST‐BE implants had a unique surface with combined micro‐/nano‐roughness and higher wettability than conventional CNC‐B implants. Histomorphometric analysis demonstrated a significant improvement in cortical bone‐implant contact of LST‐BE implants compared to CNC‐B implants after 3 and 6 weeks. However, mechanical testing revealed no differences between implant pullout forces at those time points. LST surfaces enhanced osteoblast differentiation and production of local factors in vitro and improved the osseointegration process in vivo . © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2086–2098, 2016.